Pemodelan Regresi Spline Truncated Birespon pada Inflasi dan PDRB Sumatera Utara - Sari, Atika Mayang; Sutarman, Sutarman; Rakhmawati, Fibri (Universitas Cokroaminoto Palopo, 2024)
A Nonparametric regression with a truncated biresponse spline approach is a good method in solving the problem of unknown shape of the regression curve. Truncated splines provide high flexibility in estimating curves that have data patterns that tend to change at certain intervals and do not require classic assumption tests. The purpose of this study was to obtain the best biresponse truncated spline regression model for North Sumatra's inflation and GRDP. This study uses qualitative methods and uses secondary data obtained from the Central Bureau of Statistics of North Sumatra. Selection of the best model is determined based on the optimal knot point using the minimum GCV value criteria. The research results obtained are the best spline model with 3 knot points with an MSE value of 1.6028 and a minimum GCV value of 0.0452. The value of response 1 is 14.64% and response 2 is 61.85%. This means that the ability of the predictor variable to explain the variance of the response variable is 14.64% and the remaining 61.85% is influenced by other factors.